The Unfree Market and the Law On the Immorality of Making Capitalism Unbridled Again - Byttebier, Koen (Economic and Financial Law & Policy - Shifting Insights & Values,, 2018)
This book examines how legal systems and mechanisms give shape to the capitalist economic system. In this regard, it focuses on the most important of these systems, such as monetary and financial law, company law, fiscality, contract and labour law. Further, the book provides a thorough analysis of the underlying ethical values of said legal systems and mechanisms. It also gives an overview of several potentially devastating related effects, such as poverty, the increasing polarisation between rich and poor, climate change, and mounting debts at both the public and private level. The book concludes by presenting proposals for change. Given its critical analysis of legal systems and mechanisms in connection with the value choices dictated by economic ideologies, the book will be of particular interest to legal and economic academics, researchers and students, but also to policymakers, and, more generally, to anyone with a genuine concern for how the socio-economic order will evolve.